2021
DOI: 10.1186/s12879-021-06835-9
|View full text |Cite
|
Sign up to set email alerts
|

TNFA -308G>A and IL10 -1082A>G polymorphisms seem to be predictive biomarkers of chronic HCV infection

Abstract: Background Genetic changes may induce dysregulated cytokine production and affect the progression of the chronic disease caused by the hepacivirus C (HCV) because the balance of pro- and anti-inflammatory cytokines determines the outcome of infection. This study evaluated the TNFA -308G>A and IL10 -1082A>G polymorphisms in the susceptibility and progress of chronic hepatitis C. Method The study included 101 samples from patients with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In our study, the high expression-related CA / Del genotype and CA allele were found to be significantly higher in COVID-19 patients, which can be evaluated as related to increased SOCS-1 expression and decreased anti-viral cytokine release. In a study from 2021, 14 the efficacy of the TNF-α-308G > A variant was evaluated in patients with hepatitis C virus (HCV), and it was shown that the GA genotype was protective against HCV infection but had no effect on necro-inflammatory activity or fibrosis score. Current findings show that the TNF-α gene variant distribution was not different between the patient and healthy groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the high expression-related CA / Del genotype and CA allele were found to be significantly higher in COVID-19 patients, which can be evaluated as related to increased SOCS-1 expression and decreased anti-viral cytokine release. In a study from 2021, 14 the efficacy of the TNF-α-308G > A variant was evaluated in patients with hepatitis C virus (HCV), and it was shown that the GA genotype was protective against HCV infection but had no effect on necro-inflammatory activity or fibrosis score. Current findings show that the TNF-α gene variant distribution was not different between the patient and healthy groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from 2021, 14 the efficacy of the TNF-α-308G > A variant was evaluated in patients with hepatitis C virus (HCV), and it was shown that the GA genotype was protective against HCV infection but had no effect on necro-inflammatory activity or fibrosis score. Current findings show that the TNF-α gene variant distribution was not different between the patient and healthy groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we used the genotypic and allelic frequencies described in the control samples of these studies as representative of the population of Belem (control group, CG) and used them for comparisons with our sample. Three studies were used for the TNF -308G/A polymorphism [ 20 , 21 , 22 ] with a total of 497 individuals, while for the IFNG +874T/A polymorphism, we used two studies [ 22 , 23 ] with a total of 397 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory responses caused by HCV infection can cause progressive liver disease. Some inflammatory cytokines may serve as biomarkers for monitoring disease progression and treatment outcome in patients with CHC [ 10 ]. The pathogenesis of HCV-infected patients is complicated and includes classical pathogen recognition, inflammatory activation, intrahepatic inflammatory cascade response, oxidative stress and endoplasmic reticulum stress.…”
Section: Introductionmentioning
confidence: 99%